BALANCED SCORECARD ANALYSIS AS A COMPANY PERFORMANCE MEASUREMENT TOOL (CASE STUDY AT PT TIMAH MAKMUR SEJAHTERA) - SOPIAN, Ade (Universitas of Muhammadiyah Prof. DR. HAMKA Jakarta (UHAMKA University), 2025)
This study aims to analyze the performance of PT Timah Makmur Sejahtera using the Balanced Scorecard (BSC) approach. The BSC was chosen because it can assess the company's performance comprehensively through four perspectives: financial, customer, internal business processes, and learning and growth. Data used were obtained from financial reports, customer surveys, and internal company documentation. The analysis results indicate that PT Timah Makmur Sejahtera has positive performance in both financial and customer aspects, but still needs improvement in the efficiency of internal business processes and strengthening the culture of innovation in the learning and growth perspective.